LEARNING STYLE-ALIGNED INSTRUCTIONAL STRATEGIES: ENHANCING PENDIDIKAN AGAMA KRISTEN (PAK) OUTCOMES IN ELEMENTARY CLASSROOMS - Isah Duapadang; Nurmida Catherine Sitompul; Agung Pramujiono (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to analyze the effect of learning style-based methods (visual, auditory, and kinesthetic) on the outcomes of Pendidikan Agama Kristen (PAK) for fourth-grade students at SDN Inpres Malompo, Nabire. Employing a quantitative approach with a quasi-experimental pretest-posttest design, 30 students were grouped according to their dominant learning style. Findings revealed significant improvement in posttest scores across all groups, with the auditory group achieving the highest results. These results highlight the importance of adaptive learning and differentiated strategies in elementary education.